2013
DOI: 10.1177/0193723513515888
|View full text |Cite
|
Sign up to set email alerts
|

A Fair Game for All? How Community Sports Clubs in Australia Deal With Diversity

Abstract: Diversity and equality are key issues confronting sport. This article draws on findings from qualitative research carried out in Australia to critically examine how diversity is understood and valued in community sport. The findings suggest that there is a discrepancy between the policy objectives of government and sport organizations and the way in which diversity is understood and responded to in practice. Diversity management is not being adopted widely among local sports clubs. The idea of a moral imperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 26 publications
1
44
0
Order By: Relevance
“…To analyse the power, therefore, means to visualize the standards that govern how sport clubs retain members, and who and what these standards influence, for example, offered activities, factors that encourage young adults to remain at their sport clubs. Scholars have shown that, in practice, sport clubs often emphasize one side of diversity over others in ways that often overlook or ignore the intersections between gender, culture, (dis)ability, and racial/ethnic inequalities (Spaaij et al, 2014). …”
Section: An Intersectional Frameworkmentioning
confidence: 99%
See 1 more Smart Citation
“…To analyse the power, therefore, means to visualize the standards that govern how sport clubs retain members, and who and what these standards influence, for example, offered activities, factors that encourage young adults to remain at their sport clubs. Scholars have shown that, in practice, sport clubs often emphasize one side of diversity over others in ways that often overlook or ignore the intersections between gender, culture, (dis)ability, and racial/ethnic inequalities (Spaaij et al, 2014). …”
Section: An Intersectional Frameworkmentioning
confidence: 99%
“…The reduction of diversity to a few of its many dimensions can also reflect the struggle that many clubs have expressed to operationalize diverse populations in the real world (Spaij et al, 2014). Even if a sport club believes in diversity as an institutional value, there can still be conflicts or disagreements over which types of diversity are desirable (Spaaij et al, 2014). It seems that diversity in the sport clubs was interpreted through the lens of white, middle-class, “non-disabled” individuals.…”
Section: The Individual At the Centre Of A Communitymentioning
confidence: 99%
“…Diversity is arguably one of the most important social and political issues facing sport organizations (Cunningham & Fink, 2006;Spaaij et al, 2014). Not only is managing diversity an important challenge for sport organizations but how diversity is dealt with both within and across sport organizations affects opportunities for persons with a disability in sport and their overall well-being (Spaaij et al, 2014).…”
Section: Is To Make Students Aware Of What Ada Is and To Give An Exammentioning
confidence: 99%
“…Such a focus on diversity in sport management relates in part to the proliferation of several key trends: (a) increased heterogeneity of the workforce requiring the need for employees to work with those who are different from themselves, (b) pressure for social justice, a moral obligation of organizations to accept all employees, and a growing emphasis on social inclusion of participants regardless of individual differences, and (c) the belief that promoting diversity can make good business sense and enhance organizational success by providing an organization with alternative viewpoints and opening up new markets through increased membership and revenue generation (Cunningham & Fink, 2006;Spaaij et al, 2014;Thomas & Guett, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Sport provides an interesting case to study in terms of diversity as there is a tension between performance (winning) and participation (recreation). Sports clubs contest competitions with the goal of winning which can work against the inclusion of people with diverse backgrounds and abilities (Spaaij et al, 2014).…”
Section: Sporting and Gendered Bodiesmentioning
confidence: 99%